Democracy in Reverse: The 2016 General Election in Zambia. Issue 3 (December 2016) - Goldring, Edward; Wahman, Michael
On 11 August 2016, Zambia held elections for the presidency, National Assembly, local councillors, and mayors. Concurrently, a referendum was held on whether to enhance the Bill of Rights in the Constitution of Zambia. The elections were significant for several reasons: It was the first contest under a newly amended Constitution, which introduced important changes to the electoral framework. It also marked a break with Zambia's positive historical record of arranging generally peaceful elections. Moreover, the election featured an electoral playing field that was notably tilted in favour of the incumbent party. Ultimately, the incumbent president, Edgar Lungu of the Patriotic Front, edged out opposition challenger Hakainde Hichilema of the United Party for National Development. The election was controversial and the opposition mounted an unsuccessful legal challenge to the final results. The 2016 elections represent a reversal in the quality of Zambian democracy and raise questions about the country's prospects for democratic consolidation.